Great significance of innovative research on capital for building socialist political economics with Chinese characteristics - Haiping Qiu (China Political Economy (CPE), 2020)
Purpose General Secretary Xi Jinping pointed out that to uphold and develop socialist political economics with Chinese characteristics, the authors should be guided by Marxist political economics. Design/methodology/approach It is an essential methodological principle for building a theoretical system of socialist political economics with Chinese characteristics as a "systematic economic theory". Findings To implement this principle, the authors need to understand the rich connotation of Marxist political economics and its relationship with socialist political economics with Chinese characteristics fully and correctly and unswervingly uphold and inherit, creatively transform and innovatively develop the theoretical achievements of Marxist economics, especially capital. Originality/value It is also an essential and necessary way to build a theoretical system of socialist political economics with Chinese characteristics.
Keywords: 330; Marxist economics; Marxist political economics; Capital; Socialist political economics with Chinesecharacteristics